Sosialisasi Pemanfaatan Area Kosong Metode Intercropping Lahan Kelapa Sawit Fase TBM di Desa Tanjung Rambutan Kampar Riau - Feri Agriani; Sri Oktika Syahputri; Boris Kaido; Afdhal Afdhal; Fajar Aga Wandana (PT Hakhara Akademia Indonesia, 2025)
The intercropping system on oil palm plantations in the Immature Plant (IMT) phase is a cultivation technique that utilizes the empty space between young oil palm plantations by planting other commodities with economic value. This practice not only provides additional income while the oil palm plantations have not yet entered the production period, but also plays a role in increasing soil fertility, reducing erosion, and optimizing the use of space on plantation land. Starting from this potential, this Community Service (PKM) activity aims to improve the understanding and skills of farmers in Tanjung Rambutan Village, Kampar, in applying the intercropping method on IMT land. The main problems faced by farmers are dependence on oil palm as the sole source of income, minimal knowledge of IMT land management, and limited capital and access to information. This PKM was implemented from April–June 2025 through the stages of needs surveys, extension, technical training, and evaluation. Extension was carried out through lectures, interactive discussions, leaflet distribution, and field demonstrations on land management techniques, selection of economically valuable intercrops, and plant spacing. The results of the activity showed an increase in farmers' understanding of the intercropping concept and an emerging interest in implementing the technique independently. The intercropping method has been shown to potentially increase farmer incomes during the TBM phase while improving soil quality, consistent with previous research. This program is expected to be the first step towards implementing sustainable agriculture through mentoring and further training in the region..